Neuro Elutax SV drug-eluting balloon versus Wingspan stent system in symptomatic intracranial high-grade stenosis: a single-center experience. (7th April 2018) - Gruber, Philipp; Garcia-Esperon, Carlos; Berberat, Jatta; Kahles, Timo; Hlavica, Martin; Anon, Javier; Diepers, Michael; Nedeltchev, Krassen; Remonda, Luca
Abstract : Background: Intracranial atherosclerotic disease is a well-known cause of ischemic stroke. Following the SAMMPRIS trial, medical treatment is favored over stenting. Drug-eluting balloons (DEB) are widely used in coronary angioplasty, showing better results than bare-surface balloons. There is little evidence of DEB employment in intracranial stenosis, especially of paclitaxel-eluted balloons (pDEB). The Neuro Elutax SV (Aachen Resonance) is the first CE certificated pDEB for intracranial use. Objective: To compare pDEB Neuro Elutax SV (ElutaxDEB) with the Wingspan/Gateway stent system (WingspanStent). Materials and methods: A single-center, open-label, retrospective cohort study of 19 patients with symptomatic atherosclerotic intracranial high-grade stenosis treated with either ElutaxDEB or WingspanStent from a tertiary stroke center in Switzerland. Results: Eight patients (42%) received ElutaxDEB. Median clinical follow-up was 10 months for the WingspanStent and 9.5 months for ElutaxDEB (P=0.36). No differences were found in the clinical baseline characteristics, with a median stenosis grade of 80% for the WingspanStent and 81% for the ElutaxDEB (P=0.87). The compound endpoint 'ischemic re-event and/or restenosis' was significantly lower for ElutaxDEB (13% vs 64%; P=0.03, OR 0.08 (95% CI 0.007 to 0.93; P=0.043) than for the WingspanStent. Conclusions: The ElutaxDEB may be a promising alternative treatment for patients with symptomatic high-grade intracranial stenosis showing a significantly lower rate of ischemic re-events or restenosis in comparison with the WingspanStent-treated patients with a similar safety profile. Further studies will be needed to definitively elucidate the role of pDEB in the management of symptomatic intracranial high-grade stenosis.